The Legacy of the Khmer Rouge Tribunal: Maintaining the Status Quo of Cambodia's Legal and Judicial System - Sana Ghouse, John Coughlan, Richard Smith (Amsterdam Law Forum, 2012)
The Cambodian judicial system is fraught with deficiencies. The Extraordinary Chambers in the Courts of Cambodia – established to try the leaders of the Khmer Rouge and those most responsible for the atrocities committed during the regime – has been hailed as a model court from which to bolster domestic legal and judicial reform. While the ECCC has made some steps towards providing a positive legacy - enhancing the capacity of the judiciary, addressing fair trial rights and standards of justice - in the absence of political will to address corruption and political interference, this legacy is superficial at best.